A bubbly universe - Occhionero, Franco; Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 1997)
We propose to explain the present large scale structure of the universe in terms of a first order phase transition in a two field inflation: the seeds of structure are assumed to be the ensuing strong, non-Gaussian, bubblelike inhomogeneities generated by the tunneling field. Along with this, of course, the ordinary zero-point fluctuations of the slow rolling inflaton are also present: they are seen as Gaussian and small perturbations of the microwave background on the large angular scales. We describe a biparametric model of bubbles in the matter dominated era (MDE) in which caustics form at a redshift z* in the surrounding shells and we assume that the caustics themselves are the loci of galaxy formation, i.e., the places where light is turned on. (Most likely z* will then define also the epoch of reionization.) The two parameters are then determined by the bubble’s two main features, present depth and z*. The caustics will evolve into the shells of galaxies observed today around the nearly empty and spherical voids. Among the possible scenarios we focus on two that yield late or early caustic formation. In the MDE the shells born with the caustics experience a strong overcomoving growth (the larger the deeper is the central cavity): this phenomenon may turn bubbles substantially subdominant at decoupling (i.e., filling then only a small fraction of the available space) into the dominant features by the present time, as the observations require. For compensated voids, from the Sachs-Wolfe, adiabatic, and Doppler effects, we find that the largest present radii compatible with COBE amount to ≈100h−1 Mpc in either scenario. Thus, if the large scale structure were generated by bubbles, the present luminous universe could look bubbly up to scales of the order of one hundred Mpc mimicking a fractal with dimension D≈2 without conflicting with the isotropy of the microwave background, because homogeneity is restored thereabove.
Gesehen am 20.11.2017